Production Concentration under the Market Economy - Ginevičius, Romualdas; Andriuškevičius, Algirdas (Ekonomika, 2000)
The production concentration is a contradictory process providing some advantages for industrialists, but also having some shortages. It is a form of an enterprises growth. The growth itself may have an inner and outer expressions. In the first case, an enterprises attaches the existing industrial capacities from the outside, in the second case it develops them itself. When analysing the production concentration, taking place at an enterprise, it is necessary to distinguish two aspects and the qualitative one. The first of them describes the growth of strategic resources (namely, technical equipment and personnel) characterising this process directly, and the second aspect discloses their quality. When assessing the strategic resources, which reflect directly the concentration process in an enterprise. these resource may he transformed into an actually produced and realised production quantity. which shows indirectly the production concentration at a factory. First of all the production concentration taking place at an enterprise should be analysed all only then the market concentration (which may he a global process), followed by the analysis of concentration in a branch and separate market.